2021
DOI: 10.1109/tse.2019.2893171
|View full text |Cite
|
Sign up to set email alerts
|

Too Many User-Reviews! What Should App Developers Look at First?

Abstract: Due to the rapid growth in the number of mobile applications (apps) in the past few years, succeeding in mobile app markets has become ruthless. Online app markets, such as Google Play Store, let users rate apps on a five-star scale and leave feedback. Given the importance of high star-ratings to the success of an app, it is crucial to help developers find the key topics of user-reviews that are significantly related to star-ratings of a given category. Having considered the key topics of user-reviews, app dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…Our proposal can couple the reputation scheme to indicate which security service the developer should concentrate on. Noei et al [10] investigated significant relationship between reviews and increase of star-ratings. They looked for key topics of user-reviews per category that developers should improve to achieve higher star-ratings.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposal can couple the reputation scheme to indicate which security service the developer should concentrate on. Noei et al [10] investigated significant relationship between reviews and increase of star-ratings. They looked for key topics of user-reviews per category that developers should improve to achieve higher star-ratings.…”
Section: Related Workmentioning
confidence: 99%
“…This proposal is subjective, does not exploit sentiment analysis on feedbacks and is subject to false reputation in case there are few feedbacks. Some authors rely on review analyses to reveal aspects to improve during application updates [9], [10,11]. Their interest focuses on functionality.…”
Section: Introductionmentioning
confidence: 99%
“…A recent research 14 demonstrated that each app category has a specific set of key topics (i.e., the topics appearing in app user reviews having statistically significant relationships with star ratings). However, it is still unclear what are the types of issues that are raised in app user reviews having negative impact on the star rating.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge is addressed in a number of ways including energy consumption profiling [3], developing a catalog of energy patterns [4], and investigating users' reviews discussed on app stores [11]. Previous work shows that users discuss the battery related issues (energy inefficiency or energy consumption) of the apps in their reviews [11], [9]. However, there is no work that addresses the automatic extraction of the battery related issues from users' feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of energy efficiency in mobile apps [4] and the fact that it is a main topic discussed by app users [9], we empirically studied 90 different models to extract energy-related issues from app reviews. These models include different machine learning (with various feature combinations) and deep learning models.…”
Section: Introductionmentioning
confidence: 99%